Contribution of drift and diffusion to water capacity deionization - Kudin, D.V.; Ostroushko, V.M.; Pashchenko, A.V.; Rodionov, S.V.; Yegorov, M.O.; Zavada, L.M. (Вопросы атомной науки и техники, 2021)
Drift and diffusion of ions in a cavity having the shape of oblate ellipsoid of revolution are considered. The obtained approximate relationship, between the time of drift and diffusion filling of deep cavity with ions, contains the applied voltage and the ratio of cavity size to the distance between electrodes. It shows that in the performed experiments with the device for water capacitive deionization the filling of electrodes by ions was carried out, mainly, due to diffusion.